The PALM Technique: histological findings of masked phototherapeutic keratectomy on rabbit corneas - Katsanevaki, Vikentia J (BioMed Central, 2003)
BACKGROUND: To compare the corneal healing response between conventional and phototherapeutic keratectomy through a masking agent, in rabbit corneas. METHODS: 24 adult rabbits underwent phototherapeutic keratectomy. Animals were divided in two groups: 12 received photoablation through a masking agent (PALM gel) and the remaining 12 received conventional phototherapeutic keratectomy of equal depth and served as control. Light and transmission electron microscopy was performed in specimens of both groups obtained: immediately after, four hours, one week, one, three and six months after treatment. RESULTS: Reepitheliazation was complete within five days in all eyes. Light and transmission electron microscopy did not reveal any differences of the healing process in the experimental eyes compared to the controls. CONCLUSION: Photoablation through the PALM technique did not result any evident alterations of the reepithelisation and stromal healing process.